APPLICATION OF INTELLIGENT TECHNOLOGIES IN AGRICULTURE - Dexkanova Nilufar Sagdullayevna; Murodov Nodir; Shernazarov Murod (Journals Park Publishing, 2024)
The article discusses the introduction of water-saving technologies in irrigation, information on the composition of lands and soils, the implementation of optimal agrotechnical measures and other scientific and innovative achievements, and best practices. The introduction of irrigation systems based on digital technologies in the use of water resources and their effectiveness are demonstrated.
Keywords: Android application, Drip irrigation, GSM module, Microcontroller, Smartphone and wireless sensor networks.